SIMULASI ALIRAN AIR TURBIN ULIR PEMBANGKIT LISTRIK MIKROHIDRO DENGAN VARIASI DEBIT MENGGUNAKAN SOFTWARE SOLIDWORKS - Suryadi P Sitinjak (LPPM Politeknik LP3I Medan, 2021)
Electrical energy is energy that has an important role for society. One of the benefits of electrical energy is for lighting. The need for electricity in the world today is very large. The source of energy used to obtain electricity is still mostly using oil and gas and coal, where oil and gas on earth is very limited, and at some point it is estimated that it will run out. With this problem, one of the renewable power plants that can be utilized is the MHP system (Microhydro Power Plant). MHP is a small-scale hydroelectric power plant by utilizing water from irrigation canals, dams, and rivers that have low head. The utilization of this power can be done by converting it into mechanical energy using a screw turbine type water turbine (Screw Archimedes) with a discharge of 0.01 m³/s, a length of 870 mm, a thread diameter of 350 mm, a shaft diameter of 190 mm with a shaft thickness of 5 mm, 6 blades which divided into 2 threads and a shaft tilt angle of 35°. This research was conducted to simulate the performance of a screw turbine using solidworks software. This study serves to obtain critical points due to fluid pressure on the screw turbine and to analyze the water fluid when the screw turbine is operated.